Value of a programmed investigation unit: an audit study. Issue 3 (March 1991) - Moore, A P; Blumhardt, L D
Abstract : A programmed investigation unit (PIU) was set up in a regional neuroscience centre. Its effects were assessed by measuring the savings associated with one particular investigation, myelography, which accounted for 50% of admissions to the PIU. Substantial savings appear to be possible, but accounting techniques allow wide variations in the estimated amounts. These benefits have to be measured against improvements which occurred simultaneously on the other wards.